Development of Islamic Religious Education Learning Oriented to Values Education - Mulia Rahman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Education is essentially an effort to pass on values, which will be the helpers and determinants of mankind in living life, and at the same time to improve the fate and civilization of mankind. Education for human life is an absolute need that must be met throughout life. Without education, it is impossible for a group of people to live and develop in line with their aspirations (aspirations) to progress, prosper and be happy according to their concept of life view. In Islamic education there is one thing that is very important, namely the existence of a value in education, where this value is inherent in humans both as conceptions, beliefs or standards of behavior. The value here is not in the understanding of numbers or symbols obtained from students as symbols of their achievements, but the essence of something that causes people to be chased, owned by humans to improve the quality of their resources. Islamic education should instead be developed towards the process of internalizing values (affective) coupled with cognitive aspects so that a very strong urge arises to practice and obey the teachings and basic religious values that have been internalized in students (psychomotor). The product of the purpose of this value-based education in substance is aimed at creating human beings and combining them with the concept of human nature.